2007
DOI: 10.1086/519494
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of CEP290 (NPHP6) Mutations Extend to Meckel Syndrome

Abstract: Meckel syndrome (MKS) is a rare autosomal recessive lethal condition characterized by central nervous system malformations, polydactyly, multicystic kidney dysplasia, and ductal changes of the liver. Three loci have been mapped (MKS1-MKS3), and two genes have been identified (MKS1/FLJ20345 and MKS3/TMEM67), whereas the gene at the MKS2 locus remains unknown. To identify new MKS loci, a genomewide linkage scan was performed using 10-cM-resolution microsatellite markers in eight families. The highest heterogenei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
212
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 244 publications
(224 citation statements)
references
References 25 publications
(38 reference statements)
9
212
0
1
Order By: Relevance
“…Despite two patients displaying an occipital encephalocele, no ARL13B variants have been found in Meckel syndrome fetuses (Cantagrel et al 9 and personal data), although Meckel syndrome has been shown to be the extreme lethal phenotype of JS for other genes. [29][30][31][32][33] In conclusion, we have identified a novel homozygous missense variant in ARL13B/JBTS8 in a JS patient with retinal involvement and obesity. We have shown that this variant is hypomorphic, as it is unable to rescue efficiently either the arl13b sco zebrafish phenotype or the deficiencies in Arl13b hnn MEFs.…”
Section: Discussionmentioning
confidence: 66%
“…Despite two patients displaying an occipital encephalocele, no ARL13B variants have been found in Meckel syndrome fetuses (Cantagrel et al 9 and personal data), although Meckel syndrome has been shown to be the extreme lethal phenotype of JS for other genes. [29][30][31][32][33] In conclusion, we have identified a novel homozygous missense variant in ARL13B/JBTS8 in a JS patient with retinal involvement and obesity. We have shown that this variant is hypomorphic, as it is unable to rescue efficiently either the arl13b sco zebrafish phenotype or the deficiencies in Arl13b hnn MEFs.…”
Section: Discussionmentioning
confidence: 66%
“…Despite these differences, it is apparent that sensory cells are much more susceptible to mutations in CEP290 than other ciliary systems. Nonsense mutations of CEP290 result in Joubert syndrome, characterized by retinal degeneration, cerebellar vermis aplasia, and nephronophthisis, and Meckel syndrome, an autosomal recessive lethal condition characterized by CNS, kidney, and liver malformations (15,21,22,25). Missense mutations (such as those detected in LCA and the rd16 mice), however, appear to only affect sensory systems, resulting in retinal degeneration and olfactory dysfunction in both humans and mice, with no overt kidney or cerebellar defects.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic mutations in ciliary, basal body, and centrosomal proteins lead to pleiotropic human diseases, including polycystic kidney disease, Bardet-Biedl syndrome, Senior-Loken syndrome, Meckel syndrome, and retinitis pigmentosa (RP) (2,7,(13)(14)(15). Nephrocystins are a family of ciliary proteins that are likely involved in cargo sorting during transport from the basal body to the ciliary axoneme (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…These include Ableson-helper integration-1 (AHI1), Nephrocystin-1 (NPHP1), Centrosomal protein-290 (CEP290), Transmembrane protein 67 (TMEM67) and Retinitis pigmentosa GTPase regulator-interacting protein-like (RPGRIP1L). Each of the genes encodes a modular scaffolding protein without clear enzymatic domains, but sharing several protein-interaction domains of unknown function, suggesting that they may be part of a signaling complex [28][29][30][31][32][33][34][35][36] The Joubert syndrome connection with cilia Although the function of JSRD proteins remains largely unknown, recent evidence suggests roles in either mediating the assembly/stability of cilia or mediating cargo transport within cilia. When tested directly, at least three of the encoded proteins, NPHP1, CEP290 and RPGRIP1L have demonstrated localization to the basal body or cilium [32,[35][36][37], further suggesting a role at the cilium or basal body.…”
Section: Joubert Syndrome and Related Disordersmentioning
confidence: 99%